The Relationship of Self Confidence to Students Learning Achievement - Zakia Oktafiani; Yusri Yusri (Counseling and Humanities Review, 2021)
Learning achievement is a description of the ability of student after participating in the teaching and learning process within a certain watch range. Ideally, studen who want to obtain optimal learning achievement have good level of self confidence. In fact, in the field there are still student who lack confidence in participating in the teaching and learning process at school. As a result, there are some student who have less than optimal learning achievement. This research was animed to examine the correlaion beetwen self confidence and learning achievement of senior high school students. This research was a quantitative study which involved student in SMAN 1 Kec. Suliki with a sample of 282 students. The intrument use to collect data were self confidence is questionnaire. This data was analyze using descriptive percentage techniques and Pearson Product Moment Correlation techniques. This result shows (1) students self confidence is in the high category, (2) students learning achievement is in the high category, (3) there is a significant positive relationship beetwen self confidence and student achievement. The result show that the coefficient correlation is 0,725 in the significant level of 0,000. So, the highet the self confidence student have, the highet their learning achievemen would be and vice versa.